New distribution of Arapaima gigas (Cuvier, 1829) (Osteoglossiformes: Arapaimidae) in Ecuador. (Revista Científica Ciencias Naturales y Ambientales, 2025)
Arapaima gigas has been identified for the first time in the Chongón reservoir, which is part of the National System of Protected Areas. This discovery extends the geographical distribution of the Arapaimidae family in Ecuador. Taxonomic characteristics and photographic records are presented to confirm the identification